Vector control strategies to enable equal frequency operation of the modular multilevel matrix converter - Diaz, Matias; Espinoza, Mauricio; Rojas, Felix; Wheeler, Patrick; Cardenas, Roberto (2018)
The Modular Multilevel Matrix Converter (M3C) is an ac-to-ac converter suitable for high-power applications. The control of this converter is complex, mainly when the frequencies of the ac systems connected to the ports of the converter are close or equal, because the floating capacitors can present large voltage oscillations. Therefore, this paper proposes a new Vector Control System to enable the operation of the M3C when the input-output frequencies are equal. The effectiveness of the proposal is validated through simulations and experimental results conducted with a 27 power-cell prototype.